2016
DOI: 10.1186/s12974-016-0588-5
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory profile in LRRK2-associated prodromal and clinical PD

Abstract: BackgroundThere is evidence for a relevant role of inflammation in the pathogenesis of Parkinson’s disease (PD). Mutations in the LRRK2 gene represent the most frequent genetic cause for autosomal dominant PD. LRRK2 is highly expressed in macrophages and microglia suggesting an involvement in inflammatory pathways. The objectives are to test (1) whether idiopathic PD and LRRK2-associated PD share common inflammatory pathways or present distinct profiles and (2) whether non-manifesting LRRK2 mutation carriers p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(64 citation statements)
references
References 38 publications
7
55
1
1
Order By: Relevance
“…(iv) Studies should be performed in patients with early disease to see if the same distinctions are present at that stage. Pre‐manifest LRRK2 mutation carriers were not investigated since it was previously shown that these individuals do not present elevated levels of inflammatory markers compared to healthy control individuals, even in subgroup analyses in those participants who presented prodromal symptoms of PD . (v) Longitudinal evaluations are needed to directly demonstrate the rate of progression of PD across the subtypes and to assess changes in inflammatory markers over the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(iv) Studies should be performed in patients with early disease to see if the same distinctions are present at that stage. Pre‐manifest LRRK2 mutation carriers were not investigated since it was previously shown that these individuals do not present elevated levels of inflammatory markers compared to healthy control individuals, even in subgroup analyses in those participants who presented prodromal symptoms of PD . (v) Longitudinal evaluations are needed to directly demonstrate the rate of progression of PD across the subtypes and to assess changes in inflammatory markers over the course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence for the involvement of LRRK2 in inflammatory pathways, linking PD LRRK2 to the immune system . This study evaluates whether peripheral inflammatory markers differ between predefined clinical phenotypes as proposed by Fereshtehnejad and colleagues and thereby help to explain the clinical variability.…”
Section: Introductionmentioning
confidence: 99%
“…The analyses were adjusted for covariates associated with disease prevalence and progression (age, sex, and Montreal Cognitive Assessment and olfaction scores). Age is associated with movement disorder progression [19], and gender has been demonstrated to have a significant effect on cytokine concentrations [20]. Cognitive and olfaction scores are used as defining parameters of disease [21].…”
Section: Methodsmentioning
confidence: 99%
“…We document here EMV cargo gene correction of a few genes that are relevant to both stem cell behavior and neurodegeneration, including SOD1, SOD2, HIF1a, APP, JAK2, GSK3B, and several other protein kinases (Jayapalan et al, ). Previous studies have shown a significant change in gene expression resulting from this LRRK2 mutation related to inflammation as seen in both prodromal and clinical PD in general (Brockmann et al, ). A study by Walker and colleagues has provided a detailed and extensive list of inflammation‐ and trophic molecule‐associated expressions within the substantia nigra and striatum in PD versus Lewy Body Disease and controls that can be a framework for future studies of PD‐representative EMVs that should highlight the importance of particular inflammatory networks for better diagnosis and treatment of different neurodegenerative diseases with often overlapping phenotypes (Walker et al, ).…”
Section: Discussionmentioning
confidence: 96%
“…Given the attention EMVs have received recently for their biomarkers and disease prognostic potential, their distinct phenotype, and their potential to play a therapeutic role (Candelario & Steindler, 2014;Rajendran et al, 2014, for review) efforts have been made to study the role of EMVs in the characterization of disease status and propagation of PD (Alvarez-Erviti et al, 2011;Fraser et al, 2013;Gui, Liu, Zhang, Lv, & Hu, 2015;Loov, Scherzer, Hyman, Breakefield, & Ingelsson, 2016;Tomlinson et al, 2015). Even though neural cells including astrocytes, neurons, and microglia have been well-documented to release EMVs under and/or contributing to different cellular states including lysosomal status, ER stress, and neuroinflammation (Brockmann et al, 2016;Eitan, Suire, Zhang, & Mattson, 2016;Fernandes et al, 2016;Gupta & Pulliam, 2014), the present study began as a proof-of-principle to show that: (a) we can employ methods for isolation of EMVs from iPSCs/neural progenitor cells (NPCs) and small sample volumes;…”
mentioning
confidence: 99%